Analyzing teachers’ competencies in career guidance: a systematic review - Joho, Corinne; Mok, Sog Yee; Hoffelner, Christine; Düggeli, Albert (Frontiers in Education, 2024)
While it is recognized that teachers play a vital role in supporting students in the career-planning process, their competencies in school-based career guidance remain underexplored. Understanding these competencies is important for enhancing the effectiveness of the career guidance provided by teachers. The aim of this systematic review was to collate the empirical evidence regarding teachers’ competencies in career guidance, to situate these findings within the context of a professional-competence model, and to identify significant gaps in the research. We conducted a systematic literature search in six different databases, targeting studies that focused on secondary-school teachers involved in career guidance. From an initial pool of 4,768 studies, 31 remained for a further analysis after we double coded 15 percent of the studies. This study shows that while secondary-school teachers generally hold positive attitudes toward career guidance in schools, they recognize shortcomings in their own knowledge and skill sets and express a need for further training. In contrast to teachers’ knowledge and attitudes, other aspects of professional competence, such as motivational orientations and self-regulation skills, received less attention in the analyzed papers. Finally, this review highlights a notable lack of theoretical modeling regarding teachers’ competencies in career guidance.